Amphiphilic Organic Cages: Self‐Assembly into Nanotubes and Enhanced Anion‐π Interactions. Issue 5 (13th May 2020) - Li, Zi‐Ying; Li, Chuanlong; Li, Pan; Zuo, Yong; Liu, Xiaoning; Xu, Shijun; Zou, Lingyi; Zhuang, Qixin; Gao, Shan; Liu, Xiaoyun; Zhang, Shaodong
Abstract: An amphiphilic organic cage was synthesized and used as self‐assembly synthon for the fabrication of novel functional supramolecular structures in solution. The transmission electron microscopy (TEM) results showed that this amphiphilic cage self‐assembled in aqueous solution into unilamellar nanotubes with a diameter of 29±4 nm at a concentration of 0.05 mg mL −1 . Interestingly, the self‐assembly of this cage significantly enhanced the anion‐π interactions as indicated by a remarkable increasement of association constant ( Ka ) between Cl − and this amphiphilic cage after self‐assembly. In specific, K a was increased from 223 M −1 for discrete cages in methanol to 6800 M −1 for aggregated cages after self‐assembly in water at the same concentration of 2.26×10 −5 M. A mechanism based on a synergistic effect was proposed in order to explain this self‐assembly process through enhanced anion‐π interactions. Abstract : United we are stronger : Unilamellar nanotubes were self‐assembled from novel amphiphilic organic cages. With three electron deficient V‐clefts working as anion receptors, these cages could bind Cl − ions in both discrete and self‐assembled states through anion‐π interactions. A remarkable self‐assembly phenomenon enhanced by anion‐π interactions was observed by comparing the association constants of the amphiphilic cage and Cl − in the discrete and self‐assembled states.